A shot to save the world the inside story of the life-or-death race for a Covid-19 vaccine - Zuckerman, Gregory (New York Penguin Random House, 2021)
Few were ready when a mysterious respiratory illness emerged in Wuhan, China in January 2020. Politicians, government officials, business leaders, and public-health professionals were unprepared for the most devastating pandemic in a century. Many of the world's biggest drug and vaccine makers were slow to react or couldn't muster an effective response. It was up to a small group of unlikely and untested scientists and executives to save civilization. A French businessman dismissed by many as a fabulist. A Turkish immigrant with little virus experience. A quirky Midwesterner obsessed with insect cells. A Boston scientist employing questionable techniques. A British scientist despised by his peers. Far from the limelight, each had spent years developing innovative vaccine approaches. Their work was met with skepticism and scorn. By 2020, these individuals had little proof of progress. Yet they and their colleagues wanted to be the ones to stop the virus holding the world hostage. They scrambled to turn their life's work into life-saving vaccines in a matter of months, each gunning to make the big breakthrough--and to beat each other for the glory that a vaccine guaranteed
Includes bibliographical references (pages 345-355).
Keywords: COVID-19 (Disease)--Vaccination.